Nuclear power unnecessary for climate protection: There are more cost-efficient alternatives - Claudia Kemfert; Thorsten Burandt; Karlo Hainsch; Konstantin Löffler; Pao-Yu Oei; Christian von Hirschhausen (DIW Economic Bulletin, 2017)
The world needs to continue working to protect the climate-this is generally undisputed. However, there is no agreement on which technologies should be used to decarbonize the energy sector. Many international scenarios still assume a relevant role for nuclear power in the future. However, a study by the German Institute for Economic Research shows that the Paris climate protection target- limiting global warming to below two degrees-can be achieved inexpensively without nuclear power. The results of a global energy system model indicate that no new nuclear power plants have to be built in order to meet the global climate target. It would be cheaper to use a combination of renewable energy and energy storage systems.
Keywords: L91; L95; Q4; 330; nuclear power; renewable energy; energy system model; climate policy; decarbonization